Patient Involvement in Healthcare-Associated Infection Research: A Lexical Review. (2nd April 2018) - Dadich, Ann; Wyer, Mary
Abstract : OBJECTIVE: This review examines patient involvement in healthcare-associated infection (HAI) research. Healthcare-associated infections represent an intractable issue with considerable implications for patients and staff. Participatory methodologies that involve patients in healthcare research are associated with myriad benefits. DESIGN: Lexical review. METHODS: PubMed was searched to identify all publications on patient involvement in HAI research since 2000; publications were also identified from the cited references. A lexical analysis was conducted of the methods sections of 148 publications. RESULTS: The findings reveal that HAI research that actively involves patients and members of the public is limited. CONCLUSIONS: Patient involvement is largely limited to recruitment to HAI studies rather than extended to patient involvement in research design, implementation, analysis, and/or dissemination. As such, there is considerable opportunity to further this important research area via alternative methodologies that award primacy to patient expertise and agency. Infect Control Hosp Epidemiol 2018;39:710–717